Misconception about HIV/AIDS transmission among sexually active women in emerging regions of Ethiopia - Wubshet D. Negash; Tadele Biresaw Belachew; Melak Jejaw; Misganaw Guadie Tiruneh; Kaleb Assegid Demissie; Desale B. Asmamaw; Elsa Awoke Fentie; Desalegn Anmut Bitew; Bewuketu Terefe; Rahel Mulatie Anteneh; Lemlem Daniel Buffa; Tadesse Tarik Tamir; et al. (PLoS ONE, 2025)
Background Misconceptions about how HIV is transmitted persist among sexually active women, especially in emerging regions, and pose a barrier to effective prevention and control efforts. Therefore, this study aims to assess the magnitude of misconceptions about HIV transmission and its associated factors in emerging regions of Ethiopia. Methods This study analyzed secondary data from a community based cross-sectional survey of 497 sexually active women in emerging regions of Ethiopia. Stata version 17.0 was used to analyze the data. Statistical analysis were completed after the data had been weighted. A binary logistic regression model was analyzed. Misconceptions about HIV transmission were addressed by examining whether healthy individuals can have HIV/AIDS and can contract HIV/AIDS through witchcraft, mosquito bites, or sharing AIDS-related foods. Odds ratio along with a 95% confidence interval (CI) was generated to identify factors associated with misconceptions about HIV. A p-value less than 0.05 was declared as statistical significance. Results Overall, 72.71% (95% CI: 68.62–76.46) sexually active women had misconceptions about HIV transmission. Those sexually active women from the poor household’s class (AOR = 2.10; 95% CI: 1.06, 4.13) and those women who had no history of HIV test (AOR = 1.67 95% CI: 1.01, 2.75) were more likely to have misconception about HIV transmission. Conclusion More than seven in ten sexually active women had misconceptions about HIV transmission. HIV prevention initiatives, such as voluntary HIV testing and post-test counseling, are needed to combat misconceptions about HIV transmission. Moreover, the administrative body of each region should facilitate extensive health education and campaigns to increase awareness of HIV transmission among sexually active women, particularly, those from poor households.